Exploration of Novel Genes and Alleles for Effective Biotic Stress Management in Rice - M. Sheshu Madhav (International Journal of Economic Plants)
Rice blast, is one of the most widespread and destructive diseases of rice throughout the world. Management of this disease is becoming difficult due to high degree of variability in pathogenicity of   M. grisea   isolates prevalent in India. In addition, the resistance in   in some resistant cultivars which have one major blast-resistance gene is quite short in the field. Hence, breedin g for more durably resistant cultivars has become a priority in rice improvement programmes throughout the world. Wild species of Oryza (store house of the genes) have rarely been used for the identification of blast resistance genes. Introgression of major genes coupled with strong QTLs will be the best strategy to make durable blast resistance. To identify the QTLs from wild Oryza species, we screened 326 stabilized introgression lines (ILs) of PR114 and Pusa44, which derived from the cross of various accessions of six different wild species viz. O. nivara, O. glumaepatula, O. rufipogon, O. glaberrima, O. longistaminata and O. barthii. After stringent blast disease screening at Directorate of Rice Research (DRR) for 3 seasons, and hot spot multi locations across India in All India Co-ordinated Rice Improvement Programme trials (AICRIP 2012-13) along with subsequent allelism test through linked and gene specific markers for 10 important blast resistance genes has led to the identification of nine extreme leaf and neck blast resistant ILs.